2021
DOI: 10.3390/e23050586
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Computational Methods in the Modeling of Complex Systems

Abstract: Based on the increased attention, the Special Issue aims to investigate the modeling of complex systems using artificial intelligence and computational methods [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…All these activities are concise with the global scientific modeling trend, allowing better description and recognition of complex systems [16][17][18][19].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…All these activities are concise with the global scientific modeling trend, allowing better description and recognition of complex systems [16][17][18][19].…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In the last two decades, AI-based data modeling tools have presented a remarkable performance in developing engineering solutions and optimization strategies for large-scale industrial systems overcoming the limitations of mathematical modeling tools. Our research group has also reported performance enhancement solutions developed on the component level, system level, and strategic level of a 660 MW coal power plant using advanced AI modeling tools and statistical techniques. ,, AI-based modeling and simulation algorithms can provide accurate results mined out of the high-dimensional and nonlinear interacting features of engineering systems, which can be reliably implemented in the running operation of energy systems . However, asymmetric and high-dimensional space of the data, development of efficient AI models and their validation, domain knowledge-backed experimental designs, and operating strategies are the challenges to be addressed carefully to exploit the true potential of data and AI algorithms.…”
Section: Introductionmentioning
confidence: 99%